The emerging landscape of dynamic DNA methylation in early childhood. (December 2017) - Xu, Cheng-Jian; Bonder, Marc; Söderhäll, Cilla; Bustamante, Mariona; Baïz, Nour; Gehring, Ulrike; Jankipersadsing, Soesma; van der Vlies, Pieter; van Diemen, Cleo; van Rijkom, Bianca; Just, Jocelyne; Kull, Inger; et al.
Abstract Background DNA methylation has been found to associate with disease, aging and environmental exposure, but it is unknown how genome, environment and disease influence DNA methylation dynamics in childhood. Results By analysing 538 paired DNA blood samples from children at birth and at 4–5 years old and 726 paired samples from children at 4 and 8 years old from four European birth cohorts using the Illumina Infinium Human Methylation 450 k chip, we have identified 14, 150 consistent age-differential methylation sites (a-DMSs) at epigenome-wide significance ofp < 1.14 × 10−7 . Genes with an increase in age-differential methylation were enriched in pathways related to 'development', and were more often located in bivalent transcription start site (TSS) regions, which can silence or activate expression of developmental genes. Genes with a decrease in age-differential methylation were involved in cell signalling, and enriched on H3K27ac, which can predict developmental state. Maternal smoking tended to decrease methylation levels at the identified da-DMSs. We also found 101 a-DMSs (0.71%) that were regulated by genetic variants usingcis -differential Methylation Quantitative Trait Locus (cis -dMeQTL) mapping. Moreover, a-DMS-associated genes during early development were significantly more likely to be linked with disease. Conclusion Our study provides new insights into the dynamic epigenetic landscape of the first 8 years of life.